The Effects of Engineered Aeration on Atmospheric Methane Flux From a Chesapeake Bay Tidal Tributary - Lapham, Laura L.; Hobbs, Edward A.; Testa, Jeremy M.; Heyes, Andrew; Forsyth, Melinda K.; Hodgkins, Casey; Szewczyk, Curtis; Harris, Lora A. (Frontiers in Environmental Science, 2022)
Engineered aeration is one solution for increasing oxygen concentrations in highly eutrophic estuaries that undergo seasonal hypoxia. Although there are various designs for engineered aeration, all approaches involve either destratification of the water column or direct injection of oxygen or air through fine bubble diffusion. To date, the effect of either approach on estuarine methane dynamics remains unknown. Here we tested the hypotheses that 1) bubble aeration will strip the water of methane and enhance the air-water methane flux to the atmosphere and 2) the addition of oxygen to the water column will enhance aerobic methane oxidation in the water column and potentially offset the air-water methane flux. These hypotheses were tested in Rock Creek, Maryland, a shallow-water sub-estuary to the Chesapeake Bay, using controlled, ecosystem-scale deoxygenation experiments where the water column and sediments were sampled in mid-summer, when aerators were ON, and then 1, 3, 7, and 13 days after the aerators were turned OFF. Experiments were performed under two system designs, large bubble and fine bubble approaches, using the same observational approach that combined discrete water sampling, long term water samplers (OsmoSamplers) and sediment porewater profiles. Regardless of aeration status, methane concentrations reached as high as 1,500 nM in the water column during the experiments and remained near 1,000 nM through the summer and into the fall. Since these concentrations are above atmospheric equilibrium of 3 nM, these data establish the sub-estuary as a source of methane to the atmosphere, with a maximum atmospheric flux as high as 1,500 µmol m-2 d-1, which is comparable to fluxes estimated from estuaries in general. Air-water methane fluxes were higher when the aerators were ON, over short time frames, supporting the hypothesis that aeration enhanced the atmospheric methane flux. The fine-bubble approach showed lower air-water methane fluxes compared to the larger bubble, destratification system. We found the primary source of the methane was the sediments, however, in situ methane production or an upstream methane source could not be ruled out. Overall, our measurements of methane concentrations were consistently high in all times and locations, supporting consistent methane flux to the atmosphere.